2016
DOI: 10.5543/tkda.2016.96507
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regional Pain Syndrome after transfemoral coronary balloon angioplasty

Abstract: Presently described is the case of a 55-year-old man who developed localized pain, allodynia, hyperpathia, and swelling over the right ankle joint following coronary balloon angioplasty, which had been performed via right femoral arterial access. Bone scan confirmed the diagnosis of complex regional pain syndrome. Various analgesics were administered, along with physiotherapist-assisted exercise. The present is the first reported case of complex regional pain syndrome presenting as remote postprocedural compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For what concerns vascular procedures, Lai et al described a case of CRPS I of right-hand in a 73-year-old male after a right-side transradial approach for PTCA [ 17 ] with signs and symptoms persisting for 3 months after the procedure and treated through non-pharmacological interventions. Parikh et al [ 18 ] reported a case of a 55-year-old man presenting with CRPS of the right foot and ankle after transfemoral coronary balloon angioplasty occurring few weeks after the intervention, and treated with physiotherapy and opioids; however, the authors did not report any detail about the safety and effectiveness of this therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For what concerns vascular procedures, Lai et al described a case of CRPS I of right-hand in a 73-year-old male after a right-side transradial approach for PTCA [ 17 ] with signs and symptoms persisting for 3 months after the procedure and treated through non-pharmacological interventions. Parikh et al [ 18 ] reported a case of a 55-year-old man presenting with CRPS of the right foot and ankle after transfemoral coronary balloon angioplasty occurring few weeks after the intervention, and treated with physiotherapy and opioids; however, the authors did not report any detail about the safety and effectiveness of this therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that any biological stimulus could provoke CRPS, including invasive procedures, we speculated that coronary angioplasty might be linked to the onset of CRPS. Only one case of CRPS of the ankle associated with transfemoral coronary balloon angioplasty has previously been published [ 18 ]. However, neither the potential pathophysiological mechanisms nor a specific therapeutic approach have been described.…”
Section: Discussionmentioning
confidence: 99%